Table S1-S5 from Gene Expression Profiling Identifies Two Chordoma Subtypes Associated with Distinct Molecular Mechanisms and Clinical Outcomes - Jiwei Bai (15051797) (2025)
Table S1. Genes included in the targeted DNA panel sequencing. Table S2. Differences in clinical characteristics by molecular subtype. Table S3. Distributions of mutation status in PBRM1 and SETD2 by molecular subtype in RNASeq and Nanostring datasets. Table S4. Differentially expressed genes among molecular subtypes. Table S5. GSEA results for up- and down-regulated gene sets comparing CC2 to CC1.